1999
DOI: 10.1007/s004360050590
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium oocysts in Bent mussels ( Ischadium recurvum ) in the Chesapeake Bay

Abstract: Filter-feeding molluscan shellfish can concentrate environmentally derived waterborne pathogens of humans, which can be utilized in the sanitary assessment of water quality. In the present study, oocysts of Cryptosporidium were detected in Bent mussels (Ischadium recurvum) at two Chesapeake Bay sites from which C. parvum-contaminated oysters had previously been collected. Spiking of Cryptosporidium-free blue mussel (Mytilus edulis) tissue with C. parvum oocysts showed a 51.1% recovery rate of oocysts, giving a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 9 publications
2
42
0
3
Order By: Relevance
“…Graczyk et al (2001) found oocysts of C. hominis (syns. C. parvum genotype 1; C. parvum genotype H; Morgan-Ryan et al, 2002) in naturally infected Zebra mussels (Dreissena polymorpha) from the St. Lawrence River, Quebec, Canada.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graczyk et al (2001) found oocysts of C. hominis (syns. C. parvum genotype 1; C. parvum genotype H; Morgan-Ryan et al, 2002) in naturally infected Zebra mussels (Dreissena polymorpha) from the St. Lawrence River, Quebec, Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Gomez-Bautista et al (2000) reported infective C. parvum oocysts in mussels (M. galloprovincialis) and cockles (Cerastoderma edule) from a shellfishproducing region in Spain. Graczyk et al (1999) found oocysts of Cryptosporidium sp. in Bent mussels (Ischadium recurvum) from the Chesapeake Bay.…”
Section: Discussionmentioning
confidence: 99%
“…17 Thus, it is more likely that Giardia cysts that have settled to the bottom will be ingested by clams, rather than suspended throughout the water column. This may explain why, despite the extensive ecologic surveys of Chesapeake Bay for Cryptosporidium and Giardia, the latter parasite has never been found in eastern oysters 3 or bent mussels, 33 which are exclusive filter feeders not ingesting sediments. 17 Cryptosporidium parvum oocysts have been recovered from other feral shellfish of Chesapeake Bay, i.e., oysters 3 and bent mussels.…”
Section: Discussionmentioning
confidence: 99%
“…17 Cryptosporidium parvum oocysts have been recovered from other feral shellfish of Chesapeake Bay, i.e., oysters 3 and bent mussels. 33 However, in contrast to Giardia cysts, sedimentation of Cryptosporidium oocysts in the water is extremely slow, 32 and under most natural conditions few oocysts are deposited in the sediments.…”
Section: Discussionmentioning
confidence: 99%
“…En invertebrados se ha detectado en moluscos bivalvos marinos (ostras, mejillones, berberechos) [13][14][15][16][17][18][19][20][21][22] , lo que sirve como indicador de contaminación fecal de las aguas. En Chile, el estudio de 642 moluscos bivalvos (choritos, ostras, almejas, machas) y muestras de agua salada obtenidas de playas de la Región de Valparaíso, usando microscopia y pruebas moleculares no ha detectado la presencia de ooquistes de Cryptosporidium como contaminante de agua ni mariscos (Neira P, datos no publicados).…”
Section: Correspondencia Aunclassified